2008
DOI: 10.1039/b805066j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular mass on supramolecular organisation of poly(4,4″-dioctyl-2,2′:5′,2″-terthiophene)

Abstract: The effect of the chain length on the type and extent of the 2D supramolecular organization in poly(4,4''-dioctyl-2,2':5',2''-terthiophene) (PDOTT) monomolecular layers deposited on highly oriented pyrolytic graphite (HOPG) is studied by scanning tunneling microscopy (STM) and analyzed in terms of molecular modeling. The strictly monodispersed fractions of increasing molecular mass used in this study were obtained by chromatographic fractionation of the crude product of 4,4''-dioctyl-2,2':5',2''-terthiophene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Jaroch et al [22] used STM to study the effect of molecular weight (MW) and polydispersity index on the local inhomogeneity of yet another regio-regular polythiophene, poly(4,4 00 -dioctyl-2,2 0 :5 0 ,2 00 -terthiophene) (PDOTT). This polymer has a reduced sidechain density as compared to regio-regular P3HT and therefore is able to show even better packing and excellent charge-carrier mobilities, generally higher than that found in regioregular P3HT.…”
Section: Scanning Tunneling Microscopy (Stm) and Scanning Tunneling Smentioning
confidence: 99%
See 3 more Smart Citations
“…Jaroch et al [22] used STM to study the effect of molecular weight (MW) and polydispersity index on the local inhomogeneity of yet another regio-regular polythiophene, poly(4,4 00 -dioctyl-2,2 0 :5 0 ,2 00 -terthiophene) (PDOTT). This polymer has a reduced sidechain density as compared to regio-regular P3HT and therefore is able to show even better packing and excellent charge-carrier mobilities, generally higher than that found in regioregular P3HT.…”
Section: Scanning Tunneling Microscopy (Stm) and Scanning Tunneling Smentioning
confidence: 99%
“…Eventually, this paradox was related to the difference in inhomogeneity and the nanoscale structural organization of materials with low and high MW and has become one of the manifestations of the importance of the inhomogeneity factor in establishing the performance of organic materials. Very recently, the importance of a related factor, the polydispersity index (PI), which characterizes the range of MWs found in a given polymer sample, has started to be recognized [22,27,40,41].…”
Section: Studies Of Local Crystallinitymentioning
confidence: 99%
See 2 more Smart Citations
“…15−21 In this context, several STM studies have shown the possibility of adsorption of thiophene derivatives on HOPG 20,22−34 or of polythiopenes. 35,36 Among those studies, several have reported that some oligothiophene derivatives form ordered monolayers at the liquid−graphite interface, such as alkylated oligothiophenes, 24,26 alkylated oligothiophenes with halogen substituents, 28,32 or carboxylated oligothiophenes. 20,29 These studies showed that the formation of the physisorbed monolayer strongly depends on the structure and the length of the oligothiophene and the presence of halogen substituents.…”
Section: Introductionmentioning
confidence: 99%